Using Gagene’s Model for Enhancing EFL Students Innovative Thinking - Araf, Israa Ibraheem; Hameed, Dunia Tahir (South Eastern European Journal of Public Health, 2024)
Gagne's model of instructional design is based on the information processing model of the mental events that occur when adults are presented with various stimuli and focuses on the learning outcomes and how to arrange specific instructional events to achieve those outcomes. Innovative thinking is the ability to create something new. This study aims at, assessing the average level of the (4th) year secondary school students' achievement in thinking skill; finding out if there is any significant difference between the achievement of the experimental and control group in the posttest; finding out if there is any significant difference between the experimental group's achievement at the recognition and the production levels in the posttest; finding out if there is any significant difference among the five variables, vocabulary, grammar, clarity, accuracy and precision. In order to fulfill the aims of the study, the following null hypotheses have been posted; there is a statistically significant difference between the average level of the students' achievement and theoretical level of achievement in the posttest; there is a statistically significant difference between the mean scores of the control group, who are taught according to the conventional method and the mean scores of the experimental group who are taught according to the conventional method and the mean scores of the experimental group who are taught by using of Gagne’s Model; there is a statistically significant difference between the mean scores of the experimental group's achievement at the recognition and the production levels in the posttest; there is a statistically significant difference between students' mean scores of the five variables, vocabulary, grammar, clarity, accuracy and precision in the posttest.